Students' perspectives on curriculum internationalisation policies in transition: Insights from a master's degree programme in the Netherlands. Issue 1 (2nd January 2021) - Mittelmeier, Jenna; Slof, Bert; Rienties, Bart
ABSTRACT: Although many studies have investigated the overarching benefits of curriuclum internationalisation in various forms, there have been few investigations of students' perspectives on changing university policies towards internationalisation. In this study, we considered master's students' perspectives on two changing internationalisation policies at a Dutch university: (1) the switch to English Medium Instruction (EMI) and (2) the increasing incorporation of internationally-minded materials into the curriculum. Through analysing 138 questionnaire responses, the relevancy of and comfort with internationalised content, the use of EMI, and overall teaching quality was explored. The findings suggested that, although most participants valued their overall internationalised learning experiences, factors such as students' educational backgrounds and perceived confidence using English influenced the degree to which curriculum internationalisation policies were deemed relevant to students' lives and careers. This article summarises with suggestions for university staff, programmes, and departments undergoing transition policies towards curriculum internationalisation.